Ocean Batik Biota in the Scrapframe - Suhartini, Siti; Purwandari, Retno; Hariyanto, Isbandono (Corak, 2022)
Marine life includes all living things in the sea, animals, plants, or corals. The number and diversity of types of biota living in the ocean are unique. This research aims to make artwork with batik techniques sourced from the idea of marine life with different displays, namely scrap frames. The research method used is practice-based, which is research that creates and reflects new work through practical research carried out. This research stage begins with data collection, analysis, and results. The analysis results are used as the initial material for creating a work of art. This artwork is a textile artwork with batik techniques that are collaborated with scrap frame techniques as batik works with a novelty display. This work is expected to give new ideas in creating a work of art, especially batik, able to educate, generate motivation and stimulate learning new things.